Peningkatan Perekonomian Masyarakat Penyandang Disabilitas Kabupaten Aceh Tamiang Melalui Program Pembeda Berdaya - Nurseno Dwi Putranto; Rara Ayuni Rahmadani; Oscar Mudha Kusuma (Jurnal Intervensi Sosial dan Pembangunan, 2022)
Discrimination against persons with disabilities is prevalent in society. There is a perception that disabled people are weak, powerless, and incapable of standing out and living a normal life. The difficulty of accessing decent emplopyment makes their economic condition poor since they are unable to become financially independent. Using interviews with 22 informants, this study analyzes how the Pembeda Berdaya Program is able to improve the economic condition of people with disabilities. In the context of Corporate Social Responsibility, the Pembeda Berdaya Program is a collaboration between the Government of Aceh Tamiang District, the NGO Boemi, and Pertamina EP Rantau Field. The Pembeda Berdaya Program is designed to give persons with disabilities access to financial assistance, skill enhancement opportunities, and other supportive instrument to enhance their economic and social well-beingKeywords: Empowerment, Person with Disabilities, Corporate Social Responsibility, CSR.